Akuntabilitas Islami dalam Akuntansi Syariah: Studi Pemikiran Sofyan Syafri Harahap - Mardiana Mardiana; Melany Nurul Ramadhani; Mushawwir Nanang; Masyhuri Masyhuri (Indo Publishing, 2026)
This study aims to analyze the concept of accountability in Islamic accounting based on Sofyan Syafri Harahap’s perspective. This study employs a qualitative approach using library research. Data were obtained from various written sources, such as books, scientific journals, articles, and other literature relevant to the research topic. Data collection was conducted through a documentary study, while data analysis employed content analysis using a descriptive-qualitative approach. The results indicate that accountability, as viewed by Sofyan Syafri Harahap, is a form of responsibility grounded in the principles of trust, justice, and transparency, encompassing accountability to both humanity and Allah SWT.